SKRINING DEMENSIA DAN EDUKASI POTENSI SUMBER DAYA LAUT UNTUK MENCEGAH PENYAKIT NEURODEGENERATIF PADA MASYARAKAT PESISIR DI KABUPATEN LOMBOK UTARA (KLU) - Arina Windri Rivarti; Fitriannisa Faradina Zubaedi; Herpan Syafii Harahap; Nurhidayati Nurhidayati; Legis Ocktaviana Saputri (Universitas Mataram, 2022)
Improving the quality of health services has resulted in a high elderly population. The elderly are more susceptible to various degenerative diseases, including dementia. The high prevalence of dementia is a major health issue that has an impact on global socioeconomic problems. Indonesia is one of the world's largest archipelagic countries. As an archipelago-based region, West Nusa Tenggara (NTB) has numerous marine resources that could be utilized as potential dementia therapies. This program aims to conduct health screenings for dementia and educate about the potential of marine resources for dementia treatment. This program consists of two phases. The ﬁrst phase consists of a health screening to assess the risk of dementia. This phase includes measuring blood pressure, measuring blood sugar, and evaluating cognitive performance. The second phase consists of health education regarding the potential of marine resources. Based on dementia screening revealed that 96% of participants need additional evaluation. About 47.3% of the patients were diagnosed with hypertension, 61.1% required further confirmation for diabetes mellitus, and 5.6% were diagnosed with diabetes mellitus. Health education explains the importance of marine resources in preventing degenerative diseases, the nutritional value of marine resources, and the proper treatment of marine resources as food and medication. The community's enthusiasm for health education is high. The high interest of the people was evidenced by a large number of attendees and queries asked. The community participates actively, and the programs run as intended.